Psychophysiological Benefits of Real-Time Heart Rate Feedback in Physical Education - Stöckel, Tino; Grimm, Robert (Frontiers in Psychology, 2021)
School physical education (PE) has the potential to contribute to public-health promotion and well-being, but oftentimes students’ lack of motivation towards PE or physical activity in general, especially during adolescence, diminishes or eradicates the positive effects associated with PE. Therefore, practical approaches are required that help teachers to increase or awake students intrinsic motivation towards PE, for which self-determination theory may provide the conceptual framework. In that regard, the purpose of the present study was to examine whether the use of real-time, heart rate feedback (as a method to support students’ need for autonomy and competence) during regular PE lessons has the potential to increase students’ autonomous motivation and physical effort. To achieve this, we had forty healthy adolescents between 16 and 17 years of age run for 30 minutes either with (experimental group, EG) or without (control group, CG) real-time, individualized heart rate feedback during a regular PE class and compared physical and perceived exertion as well as joy of running between the two groups. Participants were randomly assigned to the groups. Our data revealed that participants in the EG enjoyed running more than participants in the CG (joy of running was 3.20 in the EG vs. 2.63 in the CG, p = .03) despite a higher physical (163 to 178 in EG vs. 141 to 156 beats per minute in the CG, p < .001) and perceived exertion (rating of perceived exertion of 13.22 in the EG vs. 10.59 in the CG, p = .02). That means, running with real-time, individualized heart rate feedback apparently increased participants’ motivation to run and to enjoy running at higher levels of exertion. In that regard, real-time, individualized activity feedback should be implemented in regular PE classes systematically and repeatedly to create a controllable and attainable situation that allows students to actively adjust their own behavior to achieve appealing and realistic goals.